Trichotillomania / Battered child syndrome. - Trüeb, R.M. (European Journal of Pediatric Dermatology, 2018)
(...) Trichotillomania denotes the compulsion to pull one’s own hair. The diagnosis usually is not difficult, but it may take considerable effort to convince the parents of it (3). Battered child syndrome denominates any non accidental injury inflicted to a child usually by a parent, baby-sitter, or guardian. (...)